2012
DOI: 10.1073/pnas.1207358109
|View full text |Cite
|
Sign up to set email alerts
|

Modified SH2 domain to phototrap and identify phosphotyrosine proteins from subcellular sites within cells

Abstract: Spatial regulation of tyrosine phosphorylation is important for many aspects of cell biology. However, phosphotyrosine accounts for less than 1% of all phosphorylated substrates, and it is typically a very transient event in vivo. These factors complicate the identification of key tyrosine kinase substrates, especially in the context of their extraordinary spatial organization. Here, we describe an approach to identify tyrosine kinase substrates based on their subcellular distribution from within cells. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Studies using purified insulin receptor and Ras GTPases have suggested that Ras proteins may be phosphorylated on Tyr residues (37), and a recent report using the modified SH2 domain to phototrap potential Tyr residues identified Y32 and Y64 as possible sites of phosphorylation on H-Ras in vitro (27). However, the kinase responsible for and the functional significance of Ras phosphorylation remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using purified insulin receptor and Ras GTPases have suggested that Ras proteins may be phosphorylated on Tyr residues (37), and a recent report using the modified SH2 domain to phototrap potential Tyr residues identified Y32 and Y64 as possible sites of phosphorylation on H-Ras in vitro (27). However, the kinase responsible for and the functional significance of Ras phosphorylation remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Y32, Y64, Y96, and Y157 were phosphorylated by c-Src in vitro. Interestingly, a peptide array demonstrated that phosphorylated H-Ras peptides can bind to the GST-c-Abl SH2 domain, with Y32-containing peptide being the most robust (27). We next asked which N-Ras sites, if any, were phosphorylated by c-Src in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…As tyrosine residues can undergo post-translational modifications, and phenylalanine and glutamate residues might serve as mimetics of unphosphorylated and phosphorylated tyrosine, respectively, we also generated Y526F and Y526E constructs (Derkinderen et al, 2005;Uezu et al, 2012). In transiently transfected HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many nonreceptor TKs interact with targets via their SH2 or SH3 domains, and a new method for identifying SH2 and SH3 domain binding partners in the cell has recently been developed. This method takes advantage of "unnatural amino acid" (UAA) technology, in which a UV photoactivatable UAA is incorporated into a protein domain at specific sites on its ligand-interacting surface in appropriately engineered cells, allowing cross-linking to bound proteins when cells are irradiated with UV, and recovery of the tagged domains for MS analysis (Okada et al 2011;Uezu et al 2012). …”
Section: Degenerate Peptide Libraries and Target Identificationmentioning
confidence: 99%